GO-functionalized MXene towards superior anti-corrosion coating - Qiang, Yujie; Ran, Boyuan; Li, Minjiao; Xu, Qian; Peng, Jian (Journal of colloid and interface science, 2023)
[Display omitted] •A novel GO-Ti3C2Tx nanohybrid was synthesized.•GO-Ti3C2Tx strongly improved adhesion strength of epoxy coating.•GO-Ti3C2Tx endowed epoxy coating with active anti-corrosion property. MXene flakes shows the great potential in corrosion protection area owing to their lamellar structure and remarkable mechanical features. However, these flakes are highly susceptible to oxidation, which results in their structure degradation and restrict their application in anti-corrosion field. Herein, graphene oxide (GO) was used to functionalize Ti3C2Tx MXene through TiOC bonding to fabricate GO-Ti3C2Tx nanosheets, which proved by Raman, X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FT-IR). GO-Ti3C2Tx nanosheet inclusion into the epoxy coating and their corrosion performance in 3.5 wt.% NaCl solution with 5 MPa pressure was evaluated through electrochemical techniques including open circuit potential (OCP) and electrochemical impedance spectroscopy (EIS) along with salt spray. Results indicated that GO-Ti3C2Tx/EP presented superior anti-corrosion capability, the impedance modulus at low frequency (|Z|0.01 Hz) was above 108 Ω cm2 after 8 days’ immersion in 5 MPa environment, which was 2 orders of magnitude higher than that of the pure epoxy coating. Scanning electron microscope (SEM) and salt spray images demonstrated that the epoxy coating loaded with GO-Ti3C2Tx nanosheet could provide robust corrosion protection for Q235 steel via the physical barrier effect.